Cost Effective Open Educational Platform to Face the Challenge of Massification in Cadi Ayyad University - Abdellah J. Idrissi; Khalid Berrada; Rachid Bendaoud; Khadija El Kharki; Said Machwate; Abdellatif Miraoui (Iraqi Journal of Science, 2021)
This work presents the UC@MOOC project as a pedagogical innovation to face the effects of massification that are making Moroccan universities endure many constraints for the past ten years, as well as other African universities. It aims, among its objectives, to cope with the massification factor and to overcome the language difficulties encountered by students. In this project, our top priority is to reduce academic failure then we will get to the point of responding to the training’ needs. Courses are scripted and posted online which did not require many resources, so their production cost is relatively low. Audiovisual digital content also helps us to save time, and go to a hybrid teaching or even flipped classrooms in some cases. The idea is not to suppress the face-to-face courses but, instead, to place teachers at the center of this educational innovation. The online posting of free content allows students to deepen knowledge autonomously and independently. We will present the low-cost economical model that has been used to support this initiative and the challenges that we are facing. Some provided ideas on the critical success factors of this initiative will be described and discussed.